Optimizing rejection readouts in a corneal allograft transplantation model - Lapp, Thabo (Mol Vis, 2016)
PURPOSE: To evaluate the feasibility of anterior segment spectral domain optic coherence tomography (ASOCT) as rejection readout in a keratoplasty mouse model and to compare ASOCT against the current standard (i.e., a clinical score system). Furthermore, to compare both approaches with respect to intra- and inter-individual observer variability and to calculate a critical point that distinguishes between rejection and non-rejection in ASOCT analysis. METHODS: Allogeneic penetrating keratoplasties (PKs) were performed using C3H/He donor mice and BALB/c recipient mice; syngeneic transplantations served as controls using BALB/c donors and recipients. Corneal graft rejection was determined with a clinical score. ASOCT was used to determine the central thickness of the corneal grafts in the same animals. The rejection status was corroborated with histopathological examination. RESULTS: The median survival time (MST) of the corneal allografts in the wild-type BALB/c mice was 12 days. Allogeneic transplantation led to a 100% rejection rate, whereas signs of rejection after syngeneic transplantation appeared in up to 20% of the mice. Central corneal thickness (CCT) determination via customized software revealed a direct correlation with the clinical score. Receiver operating curve (ROC) analysis confirmed CCT as a valid surrogate for rejection. Calculation of the area under the curve (AUC) revealed a value of 0.88 with an optimal cut-off at 267 pixels. CONCLUSIONS: An increase in the CCT during acute allogeneic corneal graft rejection significantly correlated with the clinical surrogate parameter “corneal opacity.” ASOCT not only generates source data, but also analysis of the ASOCT data shows lower readout variability and fewer interpreter variations than the clinical score commonly used to define the time point of graft rejection in mice.